THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN STOMATOLOGY IN DETERMINING DAMAGE TO TEETH AND SOFT TISSUE CONDITION - Azizova Shirin Shavkatovna; Torayeva Jasmin Sheraliyevna (Western European Studies, 2024)
The article contains information about the importance of artificial intelligence in dentistry, which is becoming popular today.
Keywords: artificial intelligence; intraoral cameras; CNN; neural networks